Impact of Small-Holders’ cattle Fattening on Household Income generation in Fadis District of Eastern Hararghe Zone, oromia, Ethiopia - Jafer Mume Ahmed (International Journal of Agricultural Management and Development, 2018)
At the household level, livestock plays a critical economic and social role in pastoralists and at the household level, livestock plays a critical economic and social role in pastoralists and smallholder farm households. The objectives of this study were to analyze factors affecting participation in cattle fattening and its impacts on household income in Fadis district of Eastern Hararghe. Both primary and secondary data were used. The data were collected by means of a semi-structured questionnaire from 124 samples during the period of April 20-May20/ 2017. Logit estimation revealed that participation in cattle fattening is significantly influenced by five variables. Age of household head, labor force in family member, market information, access to agricultural extension services and number of livestock are significant variables which affect the participation of the household in cattle fattening practices. Propensity score matching method was applied to analyze the impact of the cattle fattening on the household income generation. In matching processes, kernel matching with 0.25 band width was resulted in relatively low pseudo-R2 with best balancing test was found to be the best matching algorithm. This method was checked for standardized bias, t-test, and joint significance level. Propensity score matching results revealed that household participated in cattle fattening practice have got 14,071 more farm income and 12,617 total household income in Ethiopian Birr (ETB) than those household that were not participated in fattening practices. This income difference shows how non-farm and off-farm income compensated for income obtained from cattle fattening activities with farm income.